The Shielding Volume Reduction in a High Dose Rate Brachytherapy Room - González Guzmán, Sandra; Montenegro Monroy, Héctor Miguel; Pérez Honorato, Jonathan; Martínez Flores, Miguel Angel; Miranda Suárez, Federico (Revista Mexicana de Ingenieria Biomedica, 2021)
This paper describes a method to reduce the shielding thickness in a high dose brachytherapy treatment room, with an Iridium-192 source, using the protocols established by the International Atomic Energy Agency in its Safety Report No. 47; calculating the volume of shielding material, without failing to comply with the radiation safety parameters established by the General Radiation Safety Regulations and regulations in force by the Comisión Nacional de Seguridad Nuclear y Salvaguardias, which acts as the regulatory body for the use of radioactive sources in Mexico. The shielding of the walls was determined as a function of room design, source activity, workload, use factor, number of weekly treatments, treatment time, and shielding material properties. The results show that the shielding volume can be reduced by 19.592% and 20.727% for five-point and eleven-point fractionation, respectively, for a Brachytherapy room with a maze.